Voltage sag compensation using D-STATCOM and DVR in distribution system / Mohd Ridhwan Abdul Rani - Abdul Rani, Mohd Ridhwan (2011)
Nowadays, power quality problems have increase concern among utilities provider and customers. This is due to customers nowadays are better informed about power quality problems and this will challenged utilities to improve power quality. Other than that, as industrial equipment becoming more complex, power quality becomes more significant even to minor voltage distinction. In term of economic reason, as a result of power quality problems, the costs of losses keep increasing with conjunction to rapid growth in high technology industries.